AN IMPROVED CROSS VENTILATION MODEL IN WINDY REGIONS - Rizk, Ahmed A.; Al- Samadony, Yasser. A.; A.kunbr, Usama.; Elwan, Mustafa.M. (European Scientific Journal, ESJ, 2015)
This study suggests a new simulated model to improve cross ventilation performance inside a single room space in the different wind velocity regions. The architectural design decisions of indoor openings and walls can achieve the stagnation and the Venturi conditions that can govern the indoor air velocities inside an indoor room space to be decreased in high wind velocity regions and to be increased in low wind velocity regions. Stagnation condition occurrence when an indoor wall faces an inlet opening can decrease indoor air velocities inside a single room space with a high indoor covered ventilation area because the spreading air mass movements have the curve shapes of the contour lines that indicate ratios of the outdoor wind velocity. Venturi condition occurrence when an inlet opening faces an outlet opening can increase indoor air velocities through the openings inside single room space with the high air flow rates because the penetrating air mass movements have the spire shapes of the contour lines that indicate ratios of the outdoor wind velocity. Hurghada City, Egypt, is selected as an example of windy regions while a single room space is selected as an example of indoor spaces for field and simulation experiments.